Doktor Zhivago - Pasternak, Boris Leonidovich, 1890-1960. (Ann Arbor : The University of Michigan Press, 1959)
Comprehensive picture of pre-revolutionary upper-class Russian society and the revolutionary transition. Deals with the life of an intellectual and his heroic effort to preserve his capacity for reflection.
HU OSA 300 - RFE/RL collection
Keywords: Russian fiction -- 20th century; Russia -- History -- Revolution, 1905-1907 -- Fiction